Properties, Physiological Functions and Applications of Starch-Lipid Complexes - Xinying ZHAO; Changqing RUAN; Zhijiang LI; Huacheng TANG; Changyuan WANG (Shipin gongye ke-ji)
Starch-lipid complexes, the fifth type of resistant starch, result from the binding of starch's long-chain segments with oils or fatty acids, which alters the original starch's structure, properties, and physiological functions. This review examines the impact of starch-lipid complex formation on the physicochemical characteristics of starch, including gelatinization, swelling, freeze-thaw stability, and rheological properties, as well as its digestive capabilities. Furthermore, it explores the physiological effects on stabilizing the intestinal environment, glucose metabolism, lipid metabolism, and mitigating neurological disorders. The applications of starch-lipid complexes in the food industry are also discussed. The distinctive properties and physiological impacts of starch-lipid complexes suggest promising prospects for future research and applications.